Investigation of the Effect of V Particles Added to Steels Manufactured by Powder Metallurgy - Erden, Mehmet Akif; Akkaş, Mehmet (All Sciences Proceedings, 2023)
Powder metallurgy (PM) production method is one of the widely used production methods. With the PM method, it has many features such as less material loss, easy production of complex parts, and secondary processing is generally not required. Stainless steels are the development of low-alloyed or unalloyed steels. Stainless steels are widely used in industry and biomaterial fields due to their advanced properties such as superior mechanical properties, resistance to corrosion, and use as a biomaterial. Graphite, iron, titanium, vanadium and tungsten carbide were used in this study. By PM method, 0.05 wt% and 0.1% V were added into graphite, iron and titanium powders. The powders were subjected to mechanical alloying process with a mechanical alloying device at 400 rpm for 30 minutes. Samples of each composition were formed by cold pressing the mixed powders with a one-way press device under 700 MPa pressure in the mold produced in ASTM –E8M standards. After pressing, it was sintered for two hours at 1250°C in an argon atmosphere gas environment. Production process, tensile test of finished samples, microstructure analyzes were done.
Keywords: 8. Economic growth